2018
DOI: 10.3390/w10091253
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation from (Blue-)Green Roofs: Assessing the Benefits of a Storage and Capillary Irrigation System Based on Measurements and Modeling

Abstract: Worldwide cities are facing increasing temperatures due to climate change and increasing urban density. Green roofs are promoted as a climate adaptation measure to lower air temperatures and improve comfort in urban areas, especially during intensive dry and warm spells. However, there is much debate on the effectiveness of this measure, because of a lack of fundamental knowledge about evaporation from different green roof systems. In this study, we investigate the water and energy balance of different roof ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…It seems that local actors assume that by implementing green roofs all potential ecosystem services and benefits are "delivered, " independent of the type of vegetated roof system used. Research in Dutch cities has already demonstrated that the level of ecosystem performance, provided by different vegetated roof systems, varies greatly depending on used materials, soils, water management systems and vegetation types (Solcerova et al, 2017;Cirkel et al, 2018). "To vegetate or not to vegetate" is no longer just the question; the actual performance of NBS should be discussed, characterized and rewarded (Dorst et al, 2019).…”
Section: Current Barriers For Nbs Application In Urban Development Prmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that local actors assume that by implementing green roofs all potential ecosystem services and benefits are "delivered, " independent of the type of vegetated roof system used. Research in Dutch cities has already demonstrated that the level of ecosystem performance, provided by different vegetated roof systems, varies greatly depending on used materials, soils, water management systems and vegetation types (Solcerova et al, 2017;Cirkel et al, 2018). "To vegetate or not to vegetate" is no longer just the question; the actual performance of NBS should be discussed, characterized and rewarded (Dorst et al, 2019).…”
Section: Current Barriers For Nbs Application In Urban Development Prmentioning
confidence: 99%
“…These man-made vegetated systems can regulate (rain)water effectively, because the growing site is designed for such performance. By improving and upgrading soil conditions, and adding additional engineering solutions like retention, capillary irrigation and water level sensing and controls, vegetated roofs boost improved water retention and detention during peak rain events and will continue to cool the urban environment for a longer period of time with retained rainwater during prolonged dry spells (Cirkel et al, 2018).…”
Section: Water Management and Levels Of Technologymentioning
confidence: 99%
“…Hence, the average outflow rate would be about 50 times smaller than the inflow rate of design events. Theoretically, water may be released, e.g., by changes in capillary action, by mechanisms applying pressure to stored water, and by evaporation of water into the atmosphere [47][48][49][50][51]. All three measures have different time-scales, and their design would need to meet the time limit on the full drawdown of the storage facility, typically specified as 48 h (such limits depend on the type of storage facility and the local rainfall regime).…”
Section: Discussionmentioning
confidence: 99%
“…Supply to the terrestrial vegetation is based on the capillary effect. Blue-green roofs of this type can achieve a significantly higher cooling effect as a result of the better availability of water relative to simple extensive green roofs [32], and they can also contribute significantly to rainwater retention [33]. In the case of wetland roofs, rainwater can be stored partly within a special plant carrier and water storage mat (see Figure 3), since these plants can actively supply oxygen to their root zones [34] via their aerenchyma tissue.…”
Section: Greywater and Rainwatermentioning
confidence: 99%